PENGARUH NILAI TAKSASI BARANG JAMINAN DAN NISBAH BAGI HASIL PEMBIAYAAN MUDHARABAH TERHADAP MINAT ANGGOTA DI BMT UGT SIDOGIRI CAPEM PESANGGARAN BANYUWANGI - Hendra Syahputra; Muhammad Fadil Marzuqi (Jurnal Ekonomi Syariah Darussalam, 2020)
This research aims to determine the effect of the value of collateral taxation and the profit sharing ratio of mudharabah financing on member interest. The research sample consisted of 30 respondents as members of mudharabah financing products at BMT UGT Sidogiri Capem Pesanggaran. The results of this study indicate that the value of the collateral assessments partially does not affect the interest of members in BMT Sidogiri Pesanggaran. By obtaining the thitung value of 0.69, while ttabel is 2.048, which means thitung ttable, and also the value of sig. equal to 0.001